Charge‐Transfer Effects of Organic Ligands on Energy Storage Performance of Oxide Nanoparticle‐Based Electrodes. (9th September 2021) - Song, Yongkwon; Lee, Seokmin; Ko, Yongmin; Huh, June; Kim, Yongju; Yeom, Bongjun; Moon, Jun Hyuk; Cho, Jinhan
Abstract: One of the most difficult challenges related to pseudocapacitive nanoparticle (PC NP)‐based energy storage electrodes with theoretically high capacity is to overcome the sluggish charge‐transfer kinetics that result from the poorly conductive PC NPs and bulky/insulating organics (i.e., organic ligands and/or polymeric binders) within the electrodes. Herein, it is reported that physical/chemical functionalities of organic ligands and their molecular‐scale coating onto NPs have considerable effects on the rate capability and capacity of oxide NP‐based pseudocapacitor electrodes. For this study, pseudocapacitive iron oxide (Fe3 O4 ) NPs are layer‐by‐layer (LbL)‐assembled with conductive indium tin oxide (ITO) NPs using various types of organic ligands (or linkers). In particular, hydrazine ligands, which have extremely small molecular size and strong chemical reducing properties, can effectively remove bulky organic ligands from the NP surface, and thus reduce the separation distance between neighboring NPs. Simultaneously, the hydrazine ligands significantly increase the number of oxygen vacancies on Fe3 O4 and ITO NPs during LbL deposition, which markedly enhances the rate capability and capacitance of the electrodes compared to other organic ligands with bulky size and/or without reducing properties. This approach can provide a fundamental basis for developing and designing various high‐performance electrochemical electrodes based on metal oxide NPs. Abstract : This work describes how the size, chemical functionality, and interfacial interaction of organic ligands affect the energy storage performance of oxide nanoparticle‐based pseudocapacitor electrodes. The charge‐transfer kinetics of pseudocapacitive and conductive oxide NP‐based electrodes can be significantly enhanced by chemical reducing ligand‐mediated layer‐by‐layer assembly, which leads to enhanced rate capability and capacity.